Out of the woods: psychophysiological investigations on wood odors to estimate their suitability as ambient scents - Schreiner, Linda; Karacan, Brid; Blankenagel, Sonja; Packhaeuser, Kai; Freiherr, Jessica; Loos, Helene (Wood Science and Technology, 2020)
Wood has been an important raw material for centuries, and humans encounter it in the form of furniture and building materials or in products of daily use. The odors emanating from such wood-based materials can add another facet to their functionality by influencing human well-being and mood. Moreover, wood odors can be used in odor-enhanced environments to foster relaxation and stress recovery. The current study was conducted to assess the subjective evaluation of, and physiological responses to, wood odors and individual wood odor constituents. The subjects smelled the odors of pine needles oil, cedar wood oil, α-pinene, and thymoquinone and evaluated the odor percept and their subjective feelings. Heart rate, finger temperature, and skin conductance were monitored throughout the experiment. The results showed that wood odors were distinct regarding their pleasantness, familiarity, and intensity. All odors enhanced the subjective feelings of happiness and content. Though no odor-specific physiological effects became evident, certain physiological measures correlated with self-reports of happy and relaxed feelings and the intensity ratings of the odors. The present study provides a basis for further studies on the use of wood odors as ambient scents and helps understanding the influence of natural odors on humans.
CRIS-Team Scopus Importer:2020-09-11